PENGEMBANGAN PASAR PRODUK OLAHAN KACANG MELALUI PERBAIKAN KEMASAN - Rhina Uchyani; Heru Irianto (UII, 2016)
Sold in the market is the key to the primary purpose of business making and development of products, which can be done with improved packaging, as with packaging that attract potential customers in turn will have an impact on the purchase decision of the product concerned. This service activities has the objective to increase the market share of processed products of beans through improved packaging, primarily on design and welding technology label packaging. The results of the banking activities is known that the welding design and packaging is done on two targets SMEs were able to improve the image of the products that have an impact on increasing the added value and the market share of products in the market.